Contexts and interculturalities. A conceptual journey through contemporary peruvian art - Gómez Apac, Hugo (2021)
This article recognizes de importance of regulation to avoid or minimize the negative externalities or damage that economic activities can generate. However, the article explains what regulatory management tools, such as the bureaucratic barriers elimination regime and the Regulatory Impact Assessment, claim as a possibility the lack of regulation, which does not mean the absence of the State. Thus, a possible scenario that public policymakers must consider is, that if the circumstances merit it, a certain economic activity could find itself exempt from regulation.